Longitudinal Assessment of Structural and Functional Changes in Rod-cone Dystrophy: A 10-year Follow-up Study - Alexis Ceecee Britten-Jones, BOptom (Hons), PhD; Chi D. Luu, BOrth (Hons), PhD; Jasleen K. Jolly, MSc, DPhil; Carla J. Abbott, BOptom, PhD; Penelope J. Allen, MBBS, FRANZCO; Tina Lamey, PhD; Terri McLaren, BSc; Jennifer A. Thompson, PhD; John De Roach, PhD; Thomas L. Edwards, PhD, FRANZCO; Lauren N. Ayton, BOptom, PhD (Ophthalmology Science, 2025)
Purpose: Emerging clinical trials for inherited retinal disease (IRD) require an understanding of long-term progression. This longitudinal study investigated the genetic diagnosis and change in retinal structure and function over 10 years in rod-cone dystrophies (RCDs). Design: Longitudinal observational follow-up study. Participants: Individuals initially diagnosed with retinitis pigmentosa who underwent baseline assessment between 2010 and 2013. Methods: Baseline and follow-up assessments included best-corrected visual acuity (VA), Goldmann visual field (GVF) perimetry, spectral-domain OCT imaging, electroretinogram, and panel-based genetic testing. Linear mixed models were used to investigate disease progression and interaction between progression rate and baseline measurement. Interocular symmetry in disease progression was assessed using intraclass correlation coefficients (ICCs). Main Outcome Measures: Change in VA, GVF area, and ellipsoid zone (EZ) width over 10 years in RCD. Results: A total of 23 participants attended follow-up (mean age 63 ± 15 years at follow-up; 48% female), with 20 classified as having RCD and 3 reclassified as having cone-rod dystrophy based on genetic diagnosis. At 10-year follow-up, only 60% of RCD participants showed progression of ≥15 letters in either or both eyes, and 40% did not meet the criteria in either eye. Between the eye with poorer versus better VA at baseline, high symmetry in disease progression was observed for GVF area (ICC = 0.87; 95% confidence interval [CI]: 0.68–0.95), and moderate interocular symmetry in disease progression was observed for VA (ICC = 0.50 [95% CI: 0.07–0.77]) and EZ width (ICC = 0.64 [95% CI: 0.25–0.85]). Baseline values influenced progression for VA and percentage change in GVF area, whereas total percentage change in EZ width did not differ across baseline values. Conclusions: Many individuals with RCD did not have a significant 15-letter decline in VA over a 10-year follow-up, highlighting the challenges of relying on VA as a measure of disease progression. Symmetry between eyes varies, emphasizing a key consideration for selection of outcome measures in IRD clinical trials. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.